Ursus Arctos e promozione territoriale: un approccio di marketing - Grilli, Gianluca; Tattoni, Clara; Notaro, Sandra; Ciolli, Marco (country:ITA, 2013)
The brown bear (Ursus arctos) is a rare species that still survive in the Italian alpine space in Trentino, thanks to “Life Ursus” reintroduction project. The presence of the brown bear is extraordinarily important since only high quality natural environments can host this plantigrade. Nevertheless, the brown bear is potentially a dangerous animal, because it can cause damages to crops and livestock while looking for food. For this reason, some people focus on the cost of hosting the brown bear species in the territory where they live and they protest against its presence. On the other hand, hosting such an endangered species has many advantages too, not only from the ecological point of view, but also connected with a good publicity for tourists. Often, Italian broadcasting companies broadcast reportages about the animal and the BBC have produced a documentary titled “Predators in your backyard”, broadcasted worldwide. These programs create a good publicity to Trentino province and may attract tourists. This contribution offers an Advertising Value Equivalent (AVE) application, through which it is assessed the advertising value of a sample of reportages broadcast in italian newscasts and the BBC documentary, in order to have an overview of what it is the general magnitude of the appearance value of the brown bear in television. L’orso bruno (Ursus arctos) è una specie in estinzione, che ancora sopravvive nell’arco alpino italiano solo nella provincia autonoma di Trento, grazie al progetto di reintroduzione “Life Ursus”. La presenza dell'orso bruno è straordinariamente importante perché solo ambienti naturali di alta qualità possono ospitare l'animale. Tuttavia, visto che l'orso può avere comportamenti potenzialmente dannosi per gli allevamenti e le coltivazioni, una parte della popolazione residente in provincia non vede di buon occhio l’animale. L’orso però può essere un fattore di attrattiva per i turisti interessati alla natura e alla possibilità di vedere l’animale nel suo ambiente naturale. Anche i ...